2017
DOI: 10.3201/eid2312.170798
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza A(H7N2) Virus in Human Exposed to Sick Cats, New York, USA, 2016

Abstract: An outbreak of influenza A(H7N2) virus in cats in a shelter in New York, NY, USA, resulted in zoonotic transmission. Virus isolated from the infected human was closely related to virus isolated from a cat; both were related to low pathogenicity avian influenza A(H7N2) viruses detected in the United States during the early 2000s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…Unlike the H7N2, H7N3 and H7N7 mainly caused only mild symptoms [10][11][12][13], the H7N4 virus led to a severe human infection, as most of the reported H7N9 patients [22]. However, distinct from the H7N9, all gene segments of the H7N4 were from influenza viruses of wild birds, where reassortments might occur.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the H7N2, H7N3 and H7N7 mainly caused only mild symptoms [10][11][12][13], the H7N4 virus led to a severe human infection, as most of the reported H7N9 patients [22]. However, distinct from the H7N9, all gene segments of the H7N4 were from influenza viruses of wild birds, where reassortments might occur.…”
Section: Resultsmentioning
confidence: 99%
“…The H7 subtype HA gene has been found in combination with all nine NA subtype genes [9]. Other influenza A subtype H7 viruses, such as H7N2, H7N3 and H7N7, were documented being capable of infecting human as well [10][11][12][13], but usually selflimiting.…”
Section: Introductionmentioning
confidence: 99%
“…Even though this seems an isolated event of AIV trespassing the human host range, it certainly reminds us the plasticity of the IAV to cross the species barrier. 98 …”
mentioning
confidence: 99%
“…The cats were subsequently moved into a separate facility to facilitate control efforts, but because of the large number of cats in the shelter it took a number of weeks to bring the outbreak under control (Blachere et al 2018). A human infection was observed in one of the veterinarians involved in the control program at the shelter, in whom virus was sampled from the respiratory tract, but no clinical disease was observed (Belser et al 2017;Marinova-Petkova et al 2017). Sequence and phylogenetic analysis showed that the virus closely matched circulating avian H7N2 in the New York area over the preceding decade (Fig.…”
Section: Outbreak Of H7n2 Influenza Avian Influenza Virus In Cats Inmentioning
confidence: 99%